Anatomical and Morphometric Criteria of Spleen in Matured Gallus gallus, forma domestica L., Columbia livia G., Coturnix coturnix L. - Dunaievska, Oksana (Innovative Biosystems and Bioengineering, 2018)
Background. The spleen, as an important organ of immunogenesis, is sensitive to changes in the external and internal environment. This property is used in environmental biomonitoring. The value of the morphological studies of the spleen increases with diseases of birds, the pathogens of which constitute a threat to human life and health. They are necessary for qualitative and safe poultry production. Proceedings on the morphometric study of the spleen of birds are fragmentary in nature. Therefore, the complex comprehensive anatomical, morphometric study of the spleen of birds is relevant. Objective. The aim of the paper is to establish the morphometric criteria of the spleen of birds in the normal state: relative weight, relative areas of white and red pulp, musculoskeletal system, immunoregulatory index. Methods. Anatomical examination of the spleen was realized with the definition of topography, linear values. Immunohistochemical, histological and cytological studies of micro- and ultramicroscopic level were carried out after fixation of material in formalin or glutaral aldehyde. The coloring of histopreparations was carried out by Ehrlich`s Hematoxylin and eosin; and by the methods of Brach and Van Gizon. Subpopulations of lymphocytes were detected using murine monoclonal antibodies. Morphometric determination of relative mass, the relative area of the structural components of the spleen (musculoskeletal system, white pulp, red pulp, lymphoid nodes) were detected in matured pigeon, chicken, quail. Results. The relative spleen mass of a pigeon is 0.022 ± 0.008%, chicken – 0.138 ± 0.01%, quail – 0.121 ± 0.03%. Radial trabeculae in a chicken spleen are absent, in the pigeon and quail are poorly developed. The relative area of the white pulp of a chicken spleen is 18.68 ± 3.75%, quail – 14.38 ± 2.58%, and pigeon – 14.93 ± 6.14%. CD4+ and CD8+ lymphocytes were localized predominantly in lymphoid sheaths near the vessels. Lymphocytes CD19+ and СD20+ are concentrated in lymphoid nodes. СD20+ cells are dominated in the pulp. An ultramicroscopic singularity of the quail’s spleen is large nucleolus in the pulp cells; pigeon, in comparison with other birds, got a greater number of autophagosomes in lymphoblasts; chicken endothelial cells have well-developed organelles of the metabolic type. Conclusions. The ratio of white pulp to red in a pigeon was 1:4.91, chicken – 1:4.19, and quail – 1:5.66. The immunoregulatory pulp index was 2.00 in a pigeon; 1.85 in a chicken; 1.73 in a quail. The obtained morphometric criteria of the spleen of birds in the normal state provide the basis for further research on the influence of environmental factors, microorganisms, pharmacological preparations for the development of a test organ system in the normal state.